Is gold a hedge and/or a safe haven?: an empirical examination of European equity and bond markets from the Euro's introduction to the COVID-19 pandemic outbreak - Vieira, Duarte Saldanha (2021)
The main objective of this dissertation is to examine if Gold acts as a Hedge or as a Safe Haven against different classes of assets such as, equity and bond markets. Our focus is on the European markets, in order to evaluate Gold’s performance since the introduction of the Euro, being the markets analysed the EuroStoxx 600, the EuroStoxx Banks, the DAX, the CAC 40, the FTSEMIB, the IBEX 35, the PSI 20, the ISEQ and the ASE, as well as German, French, Italian, Spanish, Portuguese, Irish and Greek twoand ten-years bonds. We also analyse the effect on the long run and the short/medium run periods, by performing subsamples analysis. We have used ADCC-GARCH and DCC-GARCH models to capture the Hedge ability and Quantile and Specific Periods’ Regression to the Safe Haven, applying the Bai and Perron (2003) algorithm to the subsamples. Our results show that Gold can be regarded as a Hedge for equities, with particular effects visible from the Lehman Brothers collapse onwards, as well as Strong Safe Haven properties for the most extreme negative returns (1% and 2.5% quantiles) and for some specific periods such as the Lehman Brothers collapse, the Greek bailout and the Brexit Referendum. However for the COVID-19 pandemic outbreak we do not find this property. Regarding bonds, both Hedge and Safe Haven effects are not strongly visible, being Gold characterised, at best, as weak Hedge and Safe Haven, as the issuers appear to be the drivers of this effect.